2004
DOI: 10.1002/jbm.a.30110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the difference of bone turnover on peri‐titanium implant osteogenesis in ovariectomized rats

Abstract: High and low bone turnover situations, both of which are typically observed as postmenopausal and senile osteoporosis, were created by ovariectomy (OVX), and then an investigation of whether or not the difference of bone turnover affected peri-titanium (Ti) implant osteogenesis in rats was conducted. Female rats were divided into four groups. The experimental and control groups underwent OVX or sham operations at 15 or 27 weeks of age, as high or low bone turnover groups, respectively. Ti implants were inserte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…These results imply that after 1 days, bone turnover increased with both osteoblastic and osteoclastic promotion; however, bone resorption is supposed to be more strongly promoted than formation. This is similar to findings in rats with ovariectomy-induced osteoporosis (39) . After 7 days, only BMP-2 indicated slight decrease in its expression and the expression of other proteins showed no differences from control.…”
Section: Discussionsupporting
confidence: 91%
“…These results imply that after 1 days, bone turnover increased with both osteoblastic and osteoclastic promotion; however, bone resorption is supposed to be more strongly promoted than formation. This is similar to findings in rats with ovariectomy-induced osteoporosis (39) . After 7 days, only BMP-2 indicated slight decrease in its expression and the expression of other proteins showed no differences from control.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, animal experiments already demonstrated that estrogen deficiency induced osteoporosis significantly influences the contact as made by the newly formed bone with an implant surface [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The successful outcome of dental implantation is influenced by a number of confounding factors such as the boneremodeling response, implant design and topography, clinical protocols, and the patient's level of physical activity 6,19 . Bone quality is another important factor, with a higher failure rate having been observed in implants placed at type IV bone 12,14,23 .…”
mentioning
confidence: 99%